Średniowieczne „małe ojczyzny” czy centra świata? - Bering, Piotr (Studia Europaea Gnesnensia, 2010)
Medieval Europe also had its “little homelands”. Not infrequently, they rose as far as to achieve the rank of symbolical centres. Traces of such approach may be found in literary work.